“The XII Travelers Memorial of the Southwest” in El Paso, Texas, USA: Construction of a Regional Identity in a Border City in the United States - Castillo, Gerardo (2023)
This paper examines the cultural identity expressed by The XII Travelers Memorial of the Southwest in El Paso, Texas, USA. According to the monument’sstatement, the memorial is an ongoing regional project formed by “... 12 heroic bronze monuments celebrating the multicultural contributions of both men and women to the development of the Southwest.” The paper’s argument is threefold. First, it argues that the XII Travelers project could be regarded as a collage that incorporates different historical and cultural references into a single narrative. Secondly, by doing this, the memorial blurs spatial scales and builds a regional history with El Paso at its center. Finally, the paper suggests that the construction of this heroic and multiculturalregional identity must be understood in relation to growing tourist activities and the expectations that visitors have about a Southern border area in USA. The research is based on a critical review of the materialproduced by The XII Travelers Foundation and the examination of the characters and monuments of Fray García and Juan de Oñate, the only two approved travelers of the proposed list.